Band gap tailoring and yellow band emission of Cd0.9−xMnxZn0.1S (x=0 to 0.05) nanoparticles: Influence of Mn concentration. (January 2016) - Devadoss, I.; Muthukumaran, S.
Abstract: Cd0.9 -x Mn x Zn0.1 S nanoparticles with x =0 to 0.05 were prepared by a simple chemical co-precipitation method at room temperature. Crystal structure and optical properties of the synthesized nanoparticles have been analyzed by X-ray diffraction (XRD) and UV–visible spectrophotometer. XRD confirmed the phase singularity of the synthesized material, which also confirmed the formation of Cd–Mn–Zn–S solid solution rather than secondary phase formation. Energy dispersive X-ray spectra showed the presence of Cd, Zn, Mn and S in the synthesized samples. The observed higher absorbance and lower transmittance of Mn-doped Cd0.9 Zn0.1 S than Cd0.9 Zn0.1 S is due to the size effect and also the defect states induced by Mn. The decrease in energy gap at Mn=0.01 is due the 'sp–d' exchange interactions between band electrons in CdS and the localized 'd' electrons of the Mn 2+ ions. The increase in energy gap after Mn=0.01 can be explained by the excessive carriers generated by the impurity atoms. Fourier transform infrared spectroscopy (FTIR) illustrated the vibration modes of Cd–Zn–Mn–S between the wave number 530 cm −1 and 780 cm −1 . Mn=0.01 doped sample exhibits a relatively high PL intensity and covers most of the visible region than the other samples; so desirable for LED application. The intensity ratio of the green band (GB) to Mn-related yellow band (YB) is decreased after Mn=0.01 which may be due the size effect or reduction of surface defect at higher doping concentrations.